Fatigue-induced reductions of torque and shortening velocity are muscle dependent - Cheng, A. J.; Rice, C. L. (Medicine & Science in Sports & Exercise, 2008)
Introduction: In addition to torque (force) loss during dynamic fatiguing contractions, an important aspect of fatigue is the reduction in shortening velocity. Relatively few reports have studied changes in shortening velocity in response to fatigue, and inconsistencies in the results might depend on the muscle tested. To better understand fatigue-related changes in shortening velocity in different muscles, we compared the fatigue response of two muscles in humans with different physiological properties using the same criterion for task failure.